Shared Automated Teller Machine (ATM) Network in Ethiopia: Appraisal of the Competition Concerns - Enyew, Tajebe Getaneh (Bahir Dar University Journal of Law, 2023)
Traditionally, banking transactions have been carried out manually with the help of bank tellers. Nowadays, however, financial businesses are employing advanced technologies to deliver their services efficiently. Among these technologies, ATM is a noticeable one. Using ATM, customers can make a withdrawal, balance inquiry, fund transfer, and cash deposit. Until recent times, customers have been using their bank’s proprietary ATM network only. Currently, banks interconnecting their ATM network and allow customers to access their account using the ATM terminal of any bank. The Ethiopian commercial banks have also integrated their proprietary network and allow their customers to access their account using the ATM of any member bank. Though the introduction of a shared ATM payment system in the country makes it convenient for the e-banking users, so far, there is no clarity on its impact on the market competition. The objective of this article is, therefore, to analyze the major competition concerns of shared ATM network in light of the Ethiopian general competition law and the NBE’s directive on licensing and authorization of the payment system operators. In addressing this issue, the writer employed a qualitative research approach and typically doctrinal research type. After due analysis of the issue, the writer concludes that the act of creating market monopolization in the Ethiopian national switch system, the unconditional and mandatory access to new entrants, unrestricted membership in more than one network, and the collective determination of network fees at the switch level are anticompetitive acts evolving in the Ethiopian shared ATM network market. Finally, the writer remarks that the NBE should revise its directive on licensing and authorization of the payment system operators to balance cooperation and competition in the payment network market.